Transformative change for biodiversity: A review on the contribution of landscape-oriented partnerships. (January 2023) - de Koning, Susan; Boezeman, Daan; Kaufmann, Maria; Visseren-Hamakers, Ingrid J.
Abstract: Transformative change is considered a necessity to halt biodiversity loss, as it addresses its direct and indirect drivers. Scientists, conservationists and policy makers expect that landscape-oriented partnerships are able to contribute to transformative change, assuming that landscapes provide a suitable scale for stakeholders to work in a collaborative, integrative, and tailored fashion within specific social and natural conditions. Nevertheless, empirical research assessing the role of landscape-oriented partnerships in transformative change for biodiversity is scarce. This scoping review assesses the contribution of 214 landscape-oriented partnerships to transformative change using two criteria. First, whether the activities of partnerships target the indirect drivers of biodiversity loss, and second, whether they contribute to transformative governance, which consists of integrative, inclusive, adaptive, transdisciplinary and anticipatory approaches. Our analysis shows that half of the studied landscape-oriented partnerships focus solely on the direct drivers of biodiversity loss, while the other half also focus on indirect drivers. Several indirect drivers are targeted, e.g. unsustainable farming or fishing practices, attitudes, governance structures and policies and regulations. Regarding transformative governance, partnerships generally use integrative and inclusive approaches, but less often use adaptive, transdisciplinary or anticipatory approaches. Some promising examples show that landscape-oriented partnerships can contribute to changes in important indirect drivers, such as policies and regulations, by applying a combination of integrative, inclusive, adaptive and transdisciplinary governance approaches. Landscape-oriented partnerships are not a silver bullet to enable transformative change and halt biodiversity loss, but landscape-oriented partnerships can contribute - under conditions - as a complementary arrangement in transformative biodiversity governance. Graphical abstract: Unlabelled Image Highlights: 49 % of the studied partnerships address indirect drivers of biodiversity loss. Practices, attitudes, governance and policies are being addressed. Landscape-oriented partnerships commonly use integrative and inclusive approaches. Promising examples capable of addressing indirect drivers at local and national level. Contribution to transformative change and governance is currently limited.